Clinical classification and neuro-vestibular evaluation in chronic dizziness. Issue 1 (January 2015) - Oh, Sun-Young; Kim, Do-Hyung; Yang, Tae-Ho; Shin, Byoung-Soo; Jeong, Seul-Ki
Highlights Common clinical subgroups of chronic dizziness are vestibular migraine, dysautonomia, and psychogenic. Each group of chronic dizziness showed disease-specific abnormal results in oculomotor, otolithic, autonomic function and psychology testing. Appropriate diagnostic investigation of chronic dizziness based on clinical diagnosis are relevant.